Manufacturing Flexibility: A Strategic Perspective - Gerwin, Donald (Management Science, 1993)
To help meet competitive realities operations managers need to know more about the strategic aspects of manufacturing flexibility. This paper takes steps toward meeting that need by critically reviewing the literature and establishing a research agenda for the area. A conceptual model, which places flexibility within a broad context, helps to identify certain assumptions of theoretical studies which need to be challenged. The model also provides a basis for identifying specific flexibility dimensions. The manner in which these dimensions may limit the effectiveness of a manufacturing process, and the problems in operationalizing them are discussed. Focusing next on the neglected area of applied work, concepts are presented for analyzing whether desired amounts of flexibility are being achieved and whether the potential for flexibility built into a manufacturing process is being tapped. Once more, a procedure is outlined for altering a plant's types and amounts of flexibility over time. The research agenda, which grows out of the appraisal of theoretical and applied work, indicates the value in studying generic flexibility strategies, the flexibility dimensions, methods of delivery, ways of evaluating and changing a process's flexibility, and above all measurement problems. The conclusions indicate principles for strategic research, some of which have relevance for the development of mathematical models.